Weaknesses of Fidusia Execution After Rules of the Constituonal Court Number 18/PUU-XVII/2019 - Suyanti Suyanti; Sri Budi Purwaningsih (Indonesian Journal of Law and Economics Review, 2020)
The public's need for funding is currently increasing, which is used as additional capital, then people borrow funds from financing institutions on the condition that there is a guarantee to ensure legal certainty and if the debtor has broken his promise later, the object that is guaranteed can be executed, one form of guarantee institution, namely: fiduciary guarantee. The problem examined in this research is whether the decision of the constitutional court number 18 / PUU-XVII / 2019 weakens the implementation of the fiduciary guarantee execution and what is the weakness in the implementation of the fiduciary guarantee execution. The methodology used in this research is juridical and sociological based on field data and statutory regulations which are equipped with theory and literacy then followed by field data to answer the problems studied with a statute approach and analyzed deductively. The results of the research on the execution of the fiduciary object cannot be carried out by the creditor if there is no agreement from the debtor and if it is not interpreted about the existence of a default and the debtor is not willing to give voluntarily and the execution of the execution is not easy for the creditor to do.